Political sociology for a globalizing world - Drake, Michael S., 1958- (Cambridge : Polity, 2010)
This accessible book addresses one of the twenty-first century's most important issues: the increasing lack of connection between political institutions and the social reality of our everyday lives. A gulf between popular expectations and formal politics has widened continually since the revolts against authority of 1968, the Eastern European revolutions of 1989 and the growth of new social movements. Today, popular disillusion with politics is ubiquitous. Enormous social transformations on a global scale since the 1970s have produced no fundamental change in what are considered normal political institutions such as the state, or in mainstream political ideologies and parties... -- Product Description.
Political sociology and social transformation -- Theorizing power -- From identity politics to the politics of representation -- Sovereignty and the state -- Citizens, nations and nationalisms -- Civil society and the public sphere -- Social movements -- Risk and securitization -- Cosmopolitanisms and postnational formations -- War, terror and security.
Includes bibliographical references (p. [211]-224) and index.
Keywords: Political sociology; Globalization